2011
DOI: 10.1002/ajmg.b.31166
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin‐1 gene contributes differentially to early‐ and adult‐onset forms of functional psychosis

Abstract: Dysbindin-1 is a relatively ubiquitous protein in the brain which is involved in the modulation of synaptic homeostasis. The dysbindin-1 gene (DTNBP1) has been associated with schizophrenia and bipolar disorder diagnoses. However, its contribution to the severity of the clinical and neurocognitive expression of these disorders remains controversial. We aimed to explore the association between DTNBP1 and the phenotypes which are more directly linked with the underlying biology, such as age at onset and neurocog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Clinical features of schizophrenia include the positive symptoms of psychosis involving hallucinations and delusions. An association between a DTNBP1 gene variant and early-onset psychosis has been reported (Fatjo-Vilas et al, 2011). It was theorized that psychosis could be mediated by the inappropriate encoding of memories due to a mechanism involving enhanced synaptic transmission along an altered hippocampal excitatory pathway (Tamminga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features of schizophrenia include the positive symptoms of psychosis involving hallucinations and delusions. An association between a DTNBP1 gene variant and early-onset psychosis has been reported (Fatjo-Vilas et al, 2011). It was theorized that psychosis could be mediated by the inappropriate encoding of memories due to a mechanism involving enhanced synaptic transmission along an altered hippocampal excitatory pathway (Tamminga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Its function is uncertain because it is unlikely to affect the stability of HPS4 mRNA [17]. This is reminiscent of the relevant SNPs of the DTNBP1 gene, which are mostly intronic and have been significantly implicated in the executive function of healthy controls [30], in cases belonging to early-onset families with functional psychosis disorders [65], and in the spatial working memory in patients with schizophrenia [66]. This general aspect regarding the question as to why intronic SNPs are involved in cognitive function awaits further genetic study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the haplotype of the dysbindin-1 gene was correlated with the form and severity of the psychosis [44]. Haplotypes of the dysbindin-1 gene are linked to glutaminergic dysfunctions in the hippocampal formation [43].…”
Section: Dysbindin-1mentioning
confidence: 99%